Pendampingan Guru dalam Pengembangan Media Pembelajaran Berbasis Multimedia Interaktif pada Pengelolaan Kelas dalam Jaringan - Kabatiah, Maryatun; Siagian, Liber; Wahyudi , Arief; Batubara, Abdinur; Rachman, Fazli (Medan Resource Center, 2022)
Community service activities carried out by a team from the faculty of social sciences at Universitas Negeri Medan took place at State Vocational High School 2 Tebing Tinggi. Implementation of the Community Partnership Program (hereinafter referred to as PKM) which will be carried out to support efforts to implement creative and fun learning and assist in the